Pengaruh pemanfaatan jenis dan konsentrasi lipid terhadap sifat fisik edible film komposit whey-porang - Lexy Trendy Hawa; Imam Thohari; Lilik Eka Radiati (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2013)
The study objective was to determine the effect of utilization various lipids with different concentration on physical quality of whey-porang composite edible films. The materials of the study were albumen, whey powder, porang flour and lipids (butter, margarine, beeswax and palm oil). The type of lipids were P1 (beeswax), P2 (margarine), P3 (butter) and P4 (palm oil), and its concentration were 5% and 10%.  The variables were moisture content, film thickness, tensile strength and percentage of prolongation. The treatment was designed by nested completely randomized design (CRD) and the data were analyzed by analysis of variance. The Duncan's Multiple Range Test (DMRT) was applied if there were significant differences among treatments. The study found that type of lipids with different concentration had a very highly significant differences (P<0.01) on the moisture content and the tensile strength of edible film. Meanwhile, utilization of various lipids had a significant differences (P<0.05) on the film thickness of edible film, but not on its different concentration. Besides, type of lipid did not significantly influence (P<0.05) the percentage of edible film prolongation. However, its various concentration had a very highly significant differences (P<0.01) on the percentage of edible film prolongation. It can be concluded that utilization of several lipids with various concentrations in whey-porang composite edible films could reduce moisture content, tensile strength, and percentage of composite edible films prolongation but increased the film thickness. The study suggested to use butter lipids with 5% concentration to produce good mechanical edible films. The study needs further experiment about chemical quality and sensory test.Keywords: lipid, physical quality, whey, porang, composite edible films